Effect of Vitamin E on Serum Creatinine level on Gentamicin Induced Nephrotoxicity in Long Evans rats (KYAMC Journal, 2022)
Background: The kidneys are one of the vital organs of our body to excrete metabolic waste products, drugs and chemicals in the form of urine.Objectives: This study was carried out to observe the effect of Vitamin E on gentamicin-induced nephrotoxicity by assessing serum creatinine level in Long Evans rats.Materials and Methods: The experimental study was carried out on 40 Long Evans rats of both sex with the weight ranges from 172-255 gm and the age ranges from 7 to 10 weeks. The rats were divided into four groups- Group A (control) received normal saline, group B, C and D received gentamicin for 6 days, rats of group C received vitamin E capsule for 9 days with gentamicin whereas, group D received vitamin E capsule with gentamicin for total 10 days. Serum creatinine level was measured at the end of experiment.Results: The mean (mean+ SD) serum creatinine levels in group A, B, C and D were 0.98+0.34, 2.36+ 0.44, 1.39+0.18 and 1.30+0.18 respectively. The differences between the groups were highly significant (p0.50). Serum creatinine level on the normal saline control (group A) was within normal limit (0.98mg/dl). Serum creatinine level in gentamicin treated (group B) rats were more in comparison to gentamicin and vitamin E treated rats (group C&D) and pretreatment with longer duration group (group D) showed lower serum creatinine level than the shorter one (group C) though there was no significant difference. Conclusion: Vitamin E treatment showed some protective effects against gentamicin induced nephrotoxicity. The results also indicated that effectiveness of vitamin E depends on a suitable duration of pretreatment for better protection against gentamicin-induced nephrotoxicity.KYAMC Journal Vol. 13, No. 03, October 2022: 149-152